New insights into the mechanism of phthalate-induced developmental effects. (October 2018) - Mu, Xiyan; Huang, Ying; Li, Jia; Yang, Ke; Yang, Wenbo; Shen, Gongming; Li, Xuxing; Lei, Yunlei; Pang, Sen; Wang, Chengju; Li, Xuefeng; Li, Yingren
Abstract: To investigate the biological pathways involved in phthalate-induced developmental effects, zebrafish embryos were exposed to different concentrations of di-(2-ethylhexyl) (DEHP) and di-butyl phthalate (DBP) for 96 h. Embryonic exposure to DEHP and DBP induced body length decrease, yolk sac abnormities, and immune responses (up-regulation of immune proteins and genes). The lipidomic results showed that at a concentration of 50 μg/L, DEHP and DBP significantly reduced the levels of fatty acids, triglycerides, diacylglycerol, and cholesterol. These effects are partly explained by biological pathway enrichment based on data from the transcriptional and proteomic profiles. Co-exposure to DBP and ER antagonist did not significantly relieve the toxic symptoms compared with exposure to DBP alone. This indicates that phthalate-induced developmental abnormities in zebrafish might not be mediated by the ER pathway. In conclusion, we identified the possible biological pathways that mediate phthalate-induced developmental effects and found that these effects may not be driven by estrogenic activation. Graphical abstract: Highlights: The biological processes involved in phthalates induced developmental effects were identified. Significant lipid homeostasis alteration was induced by phthalates in zebrafish embryos. The developmental effects induced by phthalates may not be driven by estrogenic activation. Abstract : Developmental abnormities and involved biological pathways post phthalates exposure towards zebrafish embryos were identified.